Damage Assessment in a SiC-fiber reinforced Ceramic Matrix Composite - Konstantinos G. Dassios; Theodore E. Matikas (Journal of Engineering)
Assessment of the fracture behavior of a SiC-fbre-reinforced barium osumilite (BMAS) ceramic matrix composite tested under static and cyclic tension conditions is reported herein. Notched specimens were used in order to limit material damage within a predefined gauge length. Imposition of successive unloading/reloading loops was found to result in an increase by 20% in material strength as compared to pure tension; the observed increase is attributed to energy dissipation from large-scale interfacial debonding phenomena that dominated the post-elastic tensile behaviour of the composite. Cyclic loading also helped establish the axial residual stress state of the fibres in the composite of tensile nature via a well-defined common intersection point of unloading-reloading cycles. A translation vector approach in the stress-strain plane was successful in establishing the residual stress-free properties of the composite and in reconciling the scatter noted in elastic properties of specimens with respect to theoretical expectations.